HOLISTIC EFFECT OF UNDERSTANDING OF MUDHARABAH FINANCING ACAD AND FINANCIAL REPORTING ASPECT ON INTEREST IN ENTREPRENEURSHIP IN THE SHARIA ECONOMIC CONTEXT - Khairil Fata; Nursyidah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to investigate the effect of a holistic understanding of mudharabah financing contracts and aspects of financial statements on entrepreneurial interest in the context of Islamic economics, especially in MSME actors. This research was conducted in the city of Lhokseumawe and used a quantitative descriptive approach involving 62 respondents who were MSMEs receiving assistance and entrepreneurship coaching. The data collection method involved the use of questionnaires, interviews, and literature study. The collected data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression tests, as well as the F test (simultaneous) and t test (partial). The results showed that only the variable understanding of financial statements (X2) had a significant influence on entrepreneurial interest. This can be seen from the results of multiple linear regression tests which show a significant value of (0.00) or less than the significance level (0.05), which indicates that understanding of financial statements has a positive effect on entrepreneurial interest. Meanwhile, understanding of the mudharabah financing contract (X1) has no significant effect on the interest in entrepreneurship. This can be seen from the results of multiple linear regression testing which shows a significant value of the X1 variable of (0.524) or greater than the significance level (0.05), which indicates that understanding of mudharabah financing agreements does not significantly affect interest in entrepreneurship. This finding contribute to further understanding of the factors that influence the interest in entrepreneurship in the context of Islamic economics, and its implications for the development of SMEs. The results of this study are expected to be the basis for increasing holistic understanding of MSME actors, especially in mudharabah financing contracts and financial reports, as an effort to strengthen entrepreneurial interest in strengthening the Islamic economy.